Acadian Literature in the 21st Century – Between Tradition and Modernity. Chronique D’une Sorciere De Vent and Pierre Bleu By Antonine Maillet - Żurawska, Anna (Studia Anglica Posnaniensia, 2020)
The aim of this article is to investigate the way in which tradition combines with modernity in Antonine Maillet’s novels Chronique d’une sorcière de vent (1999) and Pierre Bleu (2006). Having discussed the position and role of Maillet’s fiction in Acadian literature, and having presented the way this prose depends on local culture, language, and folklore, the author of the analysis focuses on the elements of the represented world which go beyond the national character of this literature and at the same time place it within contemporary world literature. At the thematic level, both novels deal with significant questions of time and memory, introducing a reflection on the concept of inheriting memory and re-presenting the past. Consequently, the novels reflect on the role and responsibility of the writer, who, as a character, constitutes a part of the represented world. In this context, writing appears as a weapon in the fight against time, death, and oblivion. At the level of composition, the analysis focuses on the novels’ complex narration, its multiple levels, numerous voices, fragmentation, and eclecticism.